Sustainable Supply Chain Finance Process in Delivering Financing for SMEs: The Case of Indonesia - Imronudin Imronudin; Javed Ghulam Hussain (International Journal of Supply Chain Management, 2020)
Abstract— SMEs play an important role in economic development in every country. However, the growths of SMEs are hampered because of their difficulties in accessing external capital. In this context, the application of the concept of sustainable supply chain in the operation strategy of SMEs seems to be a very important function. This supply chain also covers all three aspects of sustainable development: business, environmental, and social. This study aims at investigating the experience of supply chain management in evaluating the worthiness of SMEs to improve operation. Qualitative method is adopted in this research because this method is appropriate to investigate the experience. Data will be collected by conducting in-depth interview to SC managers in Central Java. Data obtained from interview then analyzed using Interpretative Phenomenological Analysis (IPA) to describe and explain the experience of SC managers in evaluating and delivering financing for SMEs. This research found that there are three major themes emerging from the analysis.  Those themes are 1) financing evaluation process, obstacles to accessing Islamic financing faced by SMEs, and decision making.